Evidence for redispersion of Ni on LaMnO3 films following high-temperature oxidation - Kwon, Ohhun; Foucher, Alexandre C.; Huang, Renjing; Stach, Eric A.; Vohs, John M.; Gorte, Raymond J. (Journal of catalysis, 2022)
[Display omitted] •LaMnO3 films formed two-dimensional crystals on CaAl2O4/γ-Al2O3 supports.•CaAl2O4 was shown to be effective in preventing formation of LaAlO3 on γ-Al2O3.•High-temperature oxidation caused Ni to uniformly spread over the LaMnO3 film.•Ni particles are highly active for CO2 reforming of methane. LaMnO3 films, 0.5-nm thick, were deposited by atomic layer deposition (ALD) onto γ-Al2O3 that had been modified with 15- wt% CaO. The CaO was shown to be effective in preventing formation of LaAlO3 that formed when La2O3 was deposited directly onto γ-Al2O3. Lattice fringes on the resulting CaAl2O4/γ-Al2O3 substrate were weakly resolved, allowing a detailed characterization of the LaMnO3 films. High-resolution transmission electron microscopy (HR-TEM) images showed that the LaMnO3 formed two-dimensional crystallites, ∼10–15 nm wide, that covered most of the surface. Crystallites with (001) and (111) orientation were clearly identified. High-temperature oxidation caused Ni to spread over the LaMnO3 film, suggesting there is a reaction of the Ni2+ cations with the perovskite lattice. Ni formed by high-temperature reduction on these films remained well dispersed and significantly more active for CO2 reforming of CH4 compared to Ni on MgAl2O4, even after repeated oxidation and reduction cycles at 1073 K. The implications of these results for understanding metal-support interactions between Ni and LaMnO3 are discussed.